Knowledge level of Hybrid Rice among farmers in Balaghat district - Rahangdale, Pavan Kumar; Bose, D. K.; Patle, Chandni (Indian Journal of Extension Education, 2018)
The present investigation entitled “a study on knowledge about hybrid rice production technology among the farmer in  Balaghat District of Madhya Pradesh” was carried out in purposively selected four blocks of to assess the knowledge  about hybrid rice growers. A total of 320 hybrid rice growers were selected randomly and data were collected through  personal interview schedule. The collected data were tabulated and analyzed statistically to draw appropriate conclusions.  The study revealed that majority of the respondents (53.75%) were found in middle age group and educated up to primary  level (25.62%) having medium size of family(59.38%). Majority of the respondents (66.25%) had medium experience of  hybrid rice cultivation. Maximum number of the respondents (49.37%) having medium size of land holdings (2.1 to 4 ha)  and have annual income between Rs. 20,001 to Rs. 40,000. Majority of the respondents (61.90%) were also obtained short  term credit from co-operative societies.
Keywords: Hybrid rice; hybrid variety; knowledge